SUSTENTABILIDADE DA ORLA DO MUNICÍPIO DE SÃO LUÍS, ESTADO DO MARANHÃO: subsídios para o planejamento e gestão costeira - SOARES, Luciana Amorim (2024)
The coastal zone presents great dynamics and complexity, encompassing ecological elements and processes directly associated with the territories that interface with the region, being essential for the maintenance of resources. The growth of urban areas and the development of human activities in these environments have generated significant impacts on ecosystem services and the dynamics of the local landscape. The city of São Luís presents a great environmental diversity present on the coast and has undergone constant changes given the increase in the urbanization process in the territory, imposing the need for studies that expand knowledge and strengthen the institutional dynamics, both of the managing body of the city's heritage Union, as well as coastal states and municipalities. In view of this, the present research aims to generate bases for the management and planning of the seafront in the municipality of São Luís, based on the delineation of its physical/spatial, socioeconomic and environmental aspects. The methodology applied was carried out using the QGIS software, to delimit the seafront, following the rules and guidelines of Decree 5,300/2004. The socioeconomic characterization was analyzed through the spatialization of data on population, per capita income, sanitation, garbage collection, illegal dumps and health units, to select the census sectors in the area of influence of the seafront. Zones were defined according to the prominent characteristics of each territory as a way of detailing to determine the influences of Land Use and Cover (UCS) and changes in the landscape. The UCS was carried out through manual vectorization of the classes for the years 2005 and 2023. For the analysis of the landscape, the geoecological state was defined, depending on the level of degradation and conservation of the systemic properties of the environment. At the same time, the waterfront was classified based on projected information from the UCS and the landscape analysis of the environment. The results demonstrate the great human influence on the coastal region of the municipality, especially in the northern portion, on the limits of the urban area. Furthermore, it shows that São Luís, despite being a coastal municipality, has a lack of management instruments for the seafront. With regard to socioeconomic characteristics, the inequality between urban and rural areas was evident, regarding the services offered and the lack of management of spaces, with the rural area being the most affected with the lack of sanitary sewage, garbage collection and health units. The UCS determined that there was an increase in the construction and dense vegetation classes and a decrease in the undergrowth, sand, mangrove, cliffs, apicum and exposed soil classes, with little variation or interference in the water class. The geoecological analysis of the landscape confirms the changes occurring as a result of increased urban occupation and changes in the various ecosystems. The classification of the coast was based on the level of urbanization of the environments. Based on the results found, it is expected to generate subsidies for better management of the coastline in the municipality of São Luís, serving as a basis for the creation of plans and projects, such as the Municipal Coastal Management Plan and the Integrated Management Plan – Waterfront Project, which directly cover and discuss the planning of the seafront territory.